Radical treatment of oligometastatic non-small cell lung cancer: Ready for prime time?. (July 2017) - Brighenti, Matteo; Petrelli, Fausto; Barni, Sandro; Conti, Barbara; Sarti, Enrico; Ratti, Margherita; Panni, Stefano; Passalacqua, Rodolfo; Bersanelli, Melissa
Abstract: Oligometastatic non-small cell lung cancer (NSCLC), defined as a disease with low metastatic burden and limited organ involvement, is conceived as an intermediate condition between a truly localised disease and a widely metastatic tumour. Traditionally, local ablative therapies (LATs), such as surgery and radiotherapy, have been limited to symptoms' palliation in advanced NSCLC. Several retrospective studies suggest that using local ablative therapy for oligometastatic disease could offer good local control of the disease and improvement in terms of progression-free survival. The first randomised study of local consolidative therapy versus maintenance therapy or observation in oligometastatic NSCLC has been recently published. The results of this phase II trial showed an impressive improvement in median progression-free survival with local therapy and a delay in the appearance of new lesions, suggesting a systemically extended benefit of consolidation therapies. Nevertheless, further confirmation of this evidence with additional future trials is needed to definitively consider the combination of local treatment techniques with novel systemic agents recently approved for NSCLC therapy, such as immune checkpoint inhibitors. Highlights: Local ablative therapies, such as surgery and radiotherapy, have been limited to symptoms' palliation in advanced NSCLC. Recent studies suggest that local therapies for the primary tumor with oligometastatic disease could improve outcome. These data should be taken in great consideration as new potential standard of care in selected NSCLC patients.